2016
DOI: 10.1007/s00253-016-7495-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and diagnostic tools for detection of Helicobacter pylori

Abstract: Helicobacter pylori is responsible for worldwide chronic bacterial infection in humans affecting approximately half of the world's population. H. pylori is associated with significant morbidity and mortality including gastric cancer. The infection has both direct and indirect impacts on economic and overall well-being of patients; hence, there is a great need for diagnostic markers that could be used in the development of diagnostic kits. Here, we briefly review general aspects of H. pylori infection and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 79 publications
0
24
0
Order By: Relevance
“…Indeed, studies have confirmed high prevalence of H. pylori (between 20% and 97%) in Middle Eastern populations, e.g., Iran, Egypt, Libya, Saudi Arabia, and Turkey [28]. This is important, as H. pylori is responsible for worldwide chronic bacterial infection affecting about half of the world’s population; is associated with morbidity/mortality; is a risk factor for gastritis, duodenitis, peptic ulcer, and other benign and malignant diseases; has direct/indirect impacts on economic and general well-being of patients; and its eradication is challenging [18, 19, 28]. Nevertheless, in contrast, while reports have suggested that H. pylori could be a cause for gastritis, others found a moderate prevalence of gastritis among adolescents undergoing LSG, but only a small number of these patients were H. pylori positive [29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies have confirmed high prevalence of H. pylori (between 20% and 97%) in Middle Eastern populations, e.g., Iran, Egypt, Libya, Saudi Arabia, and Turkey [28]. This is important, as H. pylori is responsible for worldwide chronic bacterial infection affecting about half of the world’s population; is associated with morbidity/mortality; is a risk factor for gastritis, duodenitis, peptic ulcer, and other benign and malignant diseases; has direct/indirect impacts on economic and general well-being of patients; and its eradication is challenging [18, 19, 28]. Nevertheless, in contrast, while reports have suggested that H. pylori could be a cause for gastritis, others found a moderate prevalence of gastritis among adolescents undergoing LSG, but only a small number of these patients were H. pylori positive [29].…”
Section: Discussionmentioning
confidence: 99%
“…7 HP is showing an increasing resistance for the routine medical treatments by antibiotics. 3,[10][11][12][13] Thus, HP contamination detection is considerably important to prevent infections or at least diagnose the infection at early stages rather than just after serious disease and symptoms development. HP can cause several diseases, but not all hosts will suffer from symptoms as not all HP strains are seriously pathogenic.…”
Section: Introductionmentioning
confidence: 99%
“…3,[10][11][12][13] In addition, disease development also depends on host conditions like lifestyle and diet. 3,[10][11][12][13] Thus, the main challenge in HP treatment is to diagnose infection at early stage especially for hosts most likely to develop serious HP-related diseases and in host children. 10 Additionally, diagnosing HP medium contaminations within its susceptible transition routes like food, water and communal facilities will be very important to prevent infections.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations